2018
DOI: 10.1093/emph/eoy022
|View full text |Cite
|
Sign up to set email alerts
|

Status of evolutionary medicine within the field of nutrition and dietetics

Abstract: Lay SummaryThrough an online survey of nutrition and dietetic professionals and students, we learned there is interest to incorporate evolutionary medicine into the nutrition and dietetics field and education programs.Background and objectivesEvolutionary medicine is an emerging field that examines the evolutionary significance of modern disease to develop new preventative strategies or treatments. While many areas of interest in evolutionary medicine and public health involve diet, we currently lack an unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This disconnect is an important barrier to incorporation of evolutionary explanations into patient education. For example, a survey of nutrition and dietetics professionals and students found that less than half reported that they were likely to provide an evolutionary explanation of a condition or disease to a patient or client [ 45 ]. We therefore explore how the mismatch narrative can be tailored to avoid provoking controversy among patients with barriers to acceptance of evolution.…”
Section: Potential Limitations Due To Controversy Surrounding Evolutimentioning
confidence: 99%
“…This disconnect is an important barrier to incorporation of evolutionary explanations into patient education. For example, a survey of nutrition and dietetics professionals and students found that less than half reported that they were likely to provide an evolutionary explanation of a condition or disease to a patient or client [ 45 ]. We therefore explore how the mismatch narrative can be tailored to avoid provoking controversy among patients with barriers to acceptance of evolution.…”
Section: Potential Limitations Due To Controversy Surrounding Evolutimentioning
confidence: 99%
“…It has also been successfully introduced in the curriculum of medical schools in Pakistan [ 19 ]. A survey among nutrition and dietetics professionals showed a high interest in incorporating evolutionary medicine into this field [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have evaluated the current dietary habits and behaviors of dental students in the United States [14]. Some information is known about the training and assessment of medical students, although these studies are also relatively rare [15][16][17]. As more dental and medical students incorporate diet and nutrition studies into the curriculum, it becomes more important to understand the current state of medical and dental student dietary habits to focus on specific areas of concern [18][19][20].…”
Section: Introductionmentioning
confidence: 99%